1988
DOI: 10.2165/00003088-198814040-00002
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Captopril in Healthy Subjects and in Patients with Cardiovascular Diseases

Abstract: Captopril, the first orally active inhibitor of angiotensin-converting enzyme, is used widely in the treatment of hypertension and congestive heart failure. The pharmacokinetics of this agent have been studied extensively in healthy subjects and in patients with hypertension, congestive heart failure, and chronic renal failure. Captopril contains a sulphydryl group and binds readily to albumin and other plasma proteins. The drug also forms mixed disulphides with endogenous thiol-containing compounds (cysteine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
5
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(84 citation statements)
references
References 54 publications
3
75
5
1
Order By: Relevance
“…Thus, captopril was administered to inhibit ACE activity, valsatan to counteract the remaining angiotensin activity at the receptor level, and dexamethasone to suppress the ACTH effect. The ACE inhibitor captopril was preferred because its rapid action within 60-90 min (16) and valsartan because of its high affinity to the ΑΤ-I receptor (17). Therefore, all participants received 2 mg dexamethasone, 50 mg captopril, and 320 mg valsartan at midnight, at least 2 h after the last meal the day before the early morning sampling for hormones' measurements to avoid the wellknown effect of food on these drugs adsorption.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, captopril was administered to inhibit ACE activity, valsatan to counteract the remaining angiotensin activity at the receptor level, and dexamethasone to suppress the ACTH effect. The ACE inhibitor captopril was preferred because its rapid action within 60-90 min (16) and valsartan because of its high affinity to the ΑΤ-I receptor (17). Therefore, all participants received 2 mg dexamethasone, 50 mg captopril, and 320 mg valsartan at midnight, at least 2 h after the last meal the day before the early morning sampling for hormones' measurements to avoid the wellknown effect of food on these drugs adsorption.…”
Section: Methodsmentioning
confidence: 99%
“…3 A ). In patients taking captopril, plasma concentrations do not exceed 15 m (30). Even at these low concentrations, captopril was still a potent inhibitor of endothelial cell migration, exclusively blocking directional chemotaxis ( unshaded section of Fig.…”
Section: Inhibition Of In Vivo Neovascularization By Captoprilmentioning
confidence: 99%
“…In vivo, NAC and captopril have a protective role in reperfusion injury [10,11,21]. It has been suggested that their beneficial action is due to their ability to scavenge oxygen radicals [20], thus reducing the stress on the cell and resulting in less oxidation of glutathione which is also a radical scavenger.…”
Section: Discussionmentioning
confidence: 99%
“…postulated that it is transported into the cytosol and deacetylated, thus providing more substrate for the enzyme y-glutamylcysteine synthetase and increasing the glutathione concentration in the cells [19,20]. In contrast, captopril has been found to cause an increase in intracellular glutathione oxidation in patients who responded to therapy, suggesting that it acts by facilitating direct oxidant scavenging, rather than by stimulating glutathione production [21]. Addition of exogenous reduced glutathione to human erythrocytes has been reported to stimulate the reduction of intracellular glutathione in a manner similar to NAC [22,23].…”
Section: Introductionmentioning
confidence: 99%